The State of Research in Master’s Dissertations on Sports Journalism in Spain - Rojas Torrijos, José Luis (2021)
This exploratory and descriptive article diagnoses the general state of teaching and research in university master programmes in Spain. Taking this approach as starting point, this study analyzes to what extent the dissertations developed in these master degrees are more research-oriented or just produced for professional purposes according to their syllabus and the profile of their teaching staff. To this end, a comprehensive collection of data from the eight universities that offered master programmes in sports journalism between 2017 and 2019 was required. Thus, this study examines the volume, the topics and typologies of dissertations that were defended within those last two academic years. The data collection has been accompanied by questionnaires and inquiries sent to the head professors and supervisors of these degrees. Given that all master programmes on sports journalism except for one are non-official and that a high percentage of their teaching staff work in media outlets, the findings confirm that dissertations are scarcely focused on theories nor research methods, and the addressed issues can hardly open new ways to increase the scientific production in this specific field.